Antibacterial efficacy of neem (Azadirachta illdica) against Moraxella bovis and Neisseria - BANDYOPADHYAY, SAMIRAN; SASMAL, DEBASIS; GHOSH, MONOJ K; BORA, MONJIT; BISWAS, TAPAS K; SARKAR, MIHIR (The Indian Journal of Animal Sciences, 2011)
Antibacterial efficacy of neem (Azadirachta o.f indica) against Moraxella bovis and Neisseria, was studied. N-MeoH decreased the bacterial growth in a dose-dependent manner. However, there was a distinct variability between the resistant strains and sensitive strains in their response to N-MeoH, which was more apparent in M. bovis isolates.Â